An In Situ Self‐Assembly Dual Conductive Shell Nanofiber Strain Sensor with Superior Sensitivity and Antibacterial Property. Issue 4 (18th December 2021) - Zhang, Wang; Lin, Liwei; Zhang, Ligong; Choi, Yejung; Cho, Youngseul; Chen, Tianyu; Gao, Jiefeng; Yao, Hang; Piao, Yuanzhe
Abstract: At the moment, flexible, stretchable, and wearable strain sensors have extensive application prospect in medical healthcare for their abilities to instantly and accurately monitor human health and body movements, particularly suitable for patients with joint injury and movement disorder, which have attracted more and more attention. Hence, a multifunctional conductive nanofiber composite (M‐CNC) strain sensor with reliable antibacterial property is put forward. The thermoplastic polyurethane (TPU) nanofiber is served as the substrate, decorated by acid‐modified carbon nanotubes (ACNTs) and in situ self‐assembled silver nanoflowers (AgNFs), entitling the M‐CNC with double‐shell conductive networks. The M‐CNC (TPU/ACNT/AgNF) has a stable conductivity, which is up to 7.5 × 105 S m −1 . Further, the double‐shell conductive networks have greatly enhanced the sensing performance of the M‐CNC strain sensor, possessing a useful gauge factor of 55 352, during the strain of 42% to 100%. Additionally, the outer AgNF shell structure is stable even after the cyclic test for 1000 times under the strain of 50%. The AgNF also endows the M‐CNC with great antibacterial property, indicating brilliant growth inhibition effects on Gram‐negative Pseudomonas aeruginosa and Gram‐positive Staphylococcus aureus . Abstract : A multifunctional conductive nanofiber composite (M‐CNC) strain sensor with reliable antibacterial property is put forward. It has a stable conductivity, and the double‐shell conductive networks greatly enhance the sensing performance of the M‐CNC strain sensor. The silver nanoflowers also endow the M‐CNC with antibacterial property.